The use of cross-linguistic mediation tasks in developing learners’ transversal competences - Stathopoulou, Maria; Melo-Pfeifer, Sílvia (Cahiers de l’ILOB / OLBI Journal)

(untitled) (Centre canadien d’études et de recherche en bilinguisme et aménagement linguistique (CCERBAL), 2025)
Cross-linguistic mediation, a competence introduced by the Common European Framework of Reference for Languages (CEFR) in 2001, knows a new momentum after the recent publication of the CEFR Companion Volume (CEFR-CV), in 2020, which introduces new cando statements for the teaching and assessment of mediation. Situated within the framework of plurilingual and intercultural education, mediation is intended to directly contribute to the development not only of plurilingual and pluricultural competence but also of transversal competences which have recently come to the forefront in language education. This article discusses the role of cross-linguistic mediation tasks in developing learners’ transversal competences, including digital competences, intercultural understanding, organizational skills, global citizenship, social skills, media and information literacy, teamwork, and collaboration skills. This contribution aims at highlighting the link between mediation and transversal competences through the presentation and discussion of specific task examples, drawing upon the METLA project.